Asset Freezing: Smart Sanction or Criminal Charge? - van den Broek, Melissa; Hazelhorst, Monique; de Zanger, Wouter (Utrecht Journal of International and European Law, 2011)
In this article the question is asked whether asset freezing can be qualified as a criminal charge within the meaning of Article6 ECHR and if yes, what effects this qualification may have on the legislative framework on so called smart sanctions. Byanalysing Community and EU law and case law of the European Court of Human Rights, General Court of Instance andCourt of Justice of the European Communities the authors give an overview of the notion and possible qualification of assetfreezing as a criminal charge. The article further focusses on the consequenses of qualifying asset freezing as a criminal chargeunder ECHR and EC/EU law and concludes by answering the aforementioned question.This article is a rewrite of a research paper written under supervision of prof. dr. J.A.E. Vervaele and prof. dr. C.H. Brants(Willem Pompe Institute for Criminal Law and Criminology, Utrecht University School of Law), whom the authors wouldlike to thank for their useful comments and supervision.